An investigation into the difficulties in reading comprehension skills experienced byfirst-year English-majored students at school of foreign languages - Hoang, Thu Thi; Nguyen, Uyen Thi (American Journal of Education and Learning, 2023)
The purpose of this study is to explore the difficulties in English reading comprehension skills experienced by first-year English-majored students at School of Foreign Languages (SFL) in Thai Nguyen. This is done by answering two questions: “What difficulties do the first-year English-majored students meet when dealing with reading lessons and What are feasible solutions to overcome these difficulties?” One hundred and fifty first-year English-majored students were involved in answering the survey questionnaire. The questionnaire was sent to the students with a Google form link due to COVID-19. The data was collected within one day and analyzed through the descriptive statistical percentage Microsoft Office Excel 2013. The results of the study show that most of the students dealt with three main types of problems such as the area of linguistics, reading strategies, and psychology. Reading strategies are considered to be the most difficult among the three factors above and students often find it hard to guess meaning from the context, skim and scan. To solve these problems, teachers should provide students with more chances to practise reading strategies so they can use them in the right way to improve their reading comprehension and do well in their study.